Mechanical and electromechanical properties of graphene and their potential application in MEMS. (6th January 2017) - Khan, Zulfiqar H; Kermany, Atieh R; Öchsner, Andreas; Iacopi, Francesca
Abstract: Graphene-based micro-electromechanical systems (MEMS) are very promising candidates for next generation miniaturized, lightweight, and ultra-sensitive devices. In this review, we review the progress to date of the assessment of the mechanical, electromechanical, and thermomechanical properties of graphene for application in graphene-based MEMS. Graphene possesses a plethora of outstanding properties—such as a 1 TPa Young's modulus, exceptionally high 2D failure strength that stems from its sp 2 hybridization, and strong sigma bonding between carbon atoms. Such exceptional mechanical properties can enable, for example, graphene-based sound sources capable of generating sound beyond the audible range. The recently engineered piezoelectric properties of atomic force microscope tip-pressed graphene membranes or supported graphene on SiO2 substrates, have paved the way in fabricating graphene-based nano-generators and actuators. On the other hand, graphene's piezoresistive properties have enabled miniaturized pressure and strain sensors. 2D graphene nano-mechanical resonators can potentially measure ultralow forces, charges and potentially detect single atomic masses. The exceptional tribology of graphene can play a significant role in achieving superlubricity. In addition, the highest reported thermal conductivity of graphene is amenable for use in chips and providing better performing MEMS, as heat is efficiently dissipated. On top of that, graphene membranes could be nano-perforated to realize specialized applications like DNA translocation and desalination. Finally, to ensure stability and reliability of the graphene-based MEMS, adhesion is an important mechanical property that should be considered. In general, graphene could be used as a structural material in resonators, sensors, actuators and nano-generators with better performance and sensitivity than conventional MEMS.